2017
DOI: 10.21608/ejcm.2017.4089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Safety Culture among Health Care Workers in Beni-Suef University Hospital, Egypt

Abstract: Background: Patient safety is an essential component in the quality of patient care. It remains a challenge for developing countries. Assessment of patient safety culture in healthcare organizations is becoming an integral component to improve patients' safety. Aim: To assess the perceptions of patient safety culture attitude among health-care workers in Beni-Suef University hospital. Participants and Methods: A cross sectional study was conducted from January till December 2015 using the Hospital Survey on Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…The present study revealed that the overall average percent score of safety culture is 45.4% and the total average percent positive score of the individual items ranged from 16.6 to 81.8%. This was matched with the results of a study conducted by El-Shabrawy et al in 2015 in Beni –Suef University Hospital [ 18 ], who reported a score of 40%. A similar score was reported in a study conducted by El-Sherbiny et al in El-Fayoum governorate (2020), with a score of 46.5% [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study revealed that the overall average percent score of safety culture is 45.4% and the total average percent positive score of the individual items ranged from 16.6 to 81.8%. This was matched with the results of a study conducted by El-Shabrawy et al in 2015 in Beni –Suef University Hospital [ 18 ], who reported a score of 40%. A similar score was reported in a study conducted by El-Sherbiny et al in El-Fayoum governorate (2020), with a score of 46.5% [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…It may be good to reschedule shifts and reorganize the staff. Adding handoff forms, handing off in verbal and written format is recommended [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the score of teamwork within units was the highest reported in Saudi Arabia [13]. This was also consistent with other studies at a tertiary government hospital in the Philippines [14], Egypt [15][16][17], India [18,19], Nepal [20], and primary healthcare units in Tunisia [21].…”
Section: Discussionsupporting
confidence: 89%
“…The overall average safety culture score was 57 (SD = 13.81), indicating triage nurses' negative perception of the safety culture. This score is higher than in previous studies conducted in Jordan [30], Egypt [31,32], Yemen [33], Saudi Arabia [34], Cyprus [27], Iran [35], while lower than the study from Turkey [36], Brazil [37], the USA [38], Finland [39], and the nine studied countries (Italy, Portugal, the United Kingdom, China, The Netherlands, Germany, France, Finland, and Japan) in [20]. These varying results may be associated with cultural differences, contextual conditions, sampling characteristics, and the instruments used.…”
Section: Discussioncontrasting
confidence: 73%